Design Thinking of the Use of Social Media as a Means of Da'wah Inspiration of the Prophet's Hadith - Elisah Elisah; Muhamad Dede Rodliyana (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith about the use of social media as a means of da'wah. This research method uses a qualitative type through literature and field studies with a design thinking approach. The results and discussion include the hadith as inspiration for the use of social media in delivering da'wah through visual and audiovisual media innovations. This research concludes that the hadith of the Prophet SAW. has inspirational messages according to the application of design thinking in the delivery of da'wah through today's technology.